Shep interacts with posttranscriptional regulators to control dendrite morphogenesis in sensory neurons. - Olesnicky, E.C.; Antonacci, S.; Popitsch, N.; Lybecker, M.C.; Titus, M.B.; Valadez, R.; Derkach, P.G.; Marean, A.; Miller, K.; Mathai, S.K.; Killian, D.J. (Developmental Biology, 2018)
RNA binding proteins (RBPs) mediate posttranscriptional gene regulatory events throughout development. During neurogenesis, many RBPs are required for proper dendrite morphogenesis within Drosophila sensory neurons. Despite their fundamental role in neuronal morphogenesis, little is known about the molecular mechanisms in which most RBPs participate during neurogenesis. In Drosophila, alan shepard (shep) encodes a highly conserved RBP that regulates dendrite morphogenesis in sensory neurons. Moreover, the C. elegans ortholog sup-26 has also been implicated in sensory neuron dendrite morphogenesis. Nonetheless, the molecular mechanism by which Shep/SUP-26 regulate dendrite development is not understood. Here we show that Shep interacts with the RBPs Trailer Hitch (Tral), Ypsilon schachtel (Yps), Belle (Bel), and Poly(A)-Binding Protein (PABP), to direct dendrite morphogenesis in Drosophila sensory neurons. Moreover, we identify a conserved set of Shep/SUP-26 target RNAs that include regulators of cell signaling, posttranscriptional gene regulators, and known regulators of dendrite development.